Implementation of ISPS Code Security Level 2 at the Time the Ship Entered the Pontianak Navy Line to Prevent Security Threats Load at KM. Meratus Benoa - Pratama, Lucky Riyoga; Mudiyanto, Mudiyanto; Kristiawan, Dedy (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2024)
This research aims to implement ISPS Code Security Level 2 when the ship enters the Pontianak shipping channel to prevent cargo security threats on KM. Meratus Benoa. The time used by researchers to conduct research for 11 months and 13 days, starting from March 11, 2023-24 February 2024. KM. Meratus Benoa is one type of container deck ship managed by PT Meratus Line. This research method uses qualitative methods using Phenomenological research strategies. This data source collection technique is obtained from direct observation, interviews with ship crews and several journals related to this research. The results of this study indicate that the implementation of ISPS Code Security Level 2 when the ship enters the Pontianak shipping channel to prevent cargo security threats on KM.Meratus Benoa, namely by, a) Involving various efforts and activities such as patrols, security drills and additional supervision. Crew awareness and external support are also factors that influence the effectiveness of ISPS Code Security Level 2 implementation. b) There are coordination and training efforts carried out by ship officers to improve crew preparedness in dealing with security threats. As for the efforts made to prevent cargo security threats on KM Meratus Benoa by a) Restricting access to the ship and inside the ship to prevent unauthorized access, adding bulkheads to the pilot ladder door to increase security, adding guard officers and optimal division of guard duties when the ship enters a high-risk port area. b) conducting annual security exercise trials on a regular basis.